FRI0098 Elevated multi-biomarker disease activity (MBDA) predicts relapses in ra patients in sustained remission tapering tumour necrosis factor inhibitor therapy- results from the randomized controlled retro study. (15th June 2017) - Rech, J; Hagen, M; Englbrecht, M; Haschka, J; Reiser, M; Kleyer, A; Hueber, A; Manger, B; Figuereido, C; Cobra, J Fogagnolo; Tony, H-P; Finzel, S; et al.
Abstract : Background: Tumor necrosis factor inhibitors (TNFi) are the most frequently used bDMARDs in RA patients. TNFi induces remission in a substantial numbers of patients. Once remission, particularly sustained remission is achieved the question arises whether TNFi can be successfully tapered. To date biomarkers, which can help to predict if TNFi can be tapered or stopped, remain to be developed. Objectives: To test whether residual subclinical inflammation assessed by multi-biomarker disease activity (MBDA) predicts the risk of disease relapse after tapering or stopping TNFi treatment in RA patients in sustained remission. Methods: Sub-analysis of TNFi treated patients of the RETRO study, a randomized-controlled study in RA patients in sustained (>6 month) DAS28 remission comparing 3 different DMARD treatment strategies (continuation of full dose, 50% dose tapering, stopping after 50% dose tapering). Patients were followed over one year for the occurrence of relapses as defined by leaving DAS28-ESR remission (>2.6 units) (1). Vectra-DA tests were done in the baseline samples of all patients included into the RETRO study. MBDA score was calculated according to previously defined algorithms with low MDBA score defined as <30 units and moderate to high scores as ≥30 units (2). Results: Of the 151 patients included in the RETRO study, 42 received TNFi treatment (mean age: 56 ys, 25 (60%) females, 78% concomitant csDMARDs; 69% ACPA/RF positive. Baseline demographic and disease specific characteristics of these patients were comparable to the non-TNFi treated patients of the RETRO study. 26/42 patients (62%) had low MBDA scores at baseline, while 16/42 (38%) had moderate/high scores. Relapse rates were significantly (chi square p=0.016) lower in RA patients with low MBDA scores (N=8 of 26; 31%) than in those with moderate/high scores (N=11 of 16; 69%) (Figure; left graph). When separately analyzing only patients tapering TNFi (N=29), relapse rates were moderate in RA patients with low MBDA scores (N=6 of 16; 37%) but high in those with moderate/high scores (N=10 of 13; 77%) (chi square p=0.015) (Figure; right graph). Conclusions: These data show that the majority of RA patients in sustained clinical remission with low MBDA scores can successfully taper TNFi. In contrast tapering cannot be recommended in patients with moderate to high MBDA scores, as relapse rates are high in these patients. References: Haschka J et al. Ann Rheum Dis 2016, 75;45–51. Curtis JR et al. Arthritis Care Res 2012;64:1794–803. Disclosure of Interest: None declared